Spectroscopic Characterization of Gliosarcomas—Do They Differ From Glioblastomas and Metastases?. Issue 5 (September 2016) - Raab, Peter; Pilatus, Ulrich; Hattingen, Elke; Franz, Kea; Hermann, Elvis; Zanella, Friedhelm E.; Lanfermann, Heinrich
Abstract : Objective: To evaluate the spectroscopic pattern of gliosarcomas for differentiation from glioblastomas or metastases. Methods: 1 H-nuclear magnetic resonance (NMR) spectroscopic intermediate echo time data of 5 patients with histologically proven gliosarcomas were compared with data of 17 metastases and 54 glioblastomas. Specialized 1 H-NMR spectroscopy analysis software was used offline. Lipid and macromolecular resonances between 0.9 ppm and 1.4 ppm were compared besides the main metabolites using the Mann-Whitney U test. Results: Gliosarcomas showed higher lipid and macromolecule resonances and a higher lipid-choline ratio compared with glioblastomas ( P < 0.024 and P < 0.036). Glioblastomas showed higher creatine concentrations compared with metastases ( P < 0.007) but not compared with gliosarcomas. We found no significant differences between metastases and gliosarcomas. Conclusions: Gliosarcomas may mimic metastases on 1 H NMR spectroscopy showing high signal intensities from lipid and macromolecule resonances. This tumor type should be suspected if conventional imaging suggests an intra-axial brain neoplasm in combination with high lipids in solid tumor parts.